Disseminated cryptococcosis resembling miliary tuberculosis in a patient with acute myeloid leukemia. Issue 11 (November 2020) - Kurata, Keiji; Nishimura, Sho; Higashime, Ako; Kawaguchi, Koji; Nagao, Shigeki; Kozuki, Yoko; Sai, Satoshi; Yakushijin, Kimikazu; Yamamoto, Katsuya; Ito, Mitsuhiro; Matsuoka, Hiroshi; Minami, Hironobu
Abstract: Disseminated cryptococcosis, usually involving the lungs and central nervous system, carries a high risk of morbidity and mortality in immunocompromised hosts. In this report, we describe a case of miliary pulmonary cryptococcosis in a patient with acute myeloid leukemia, initially resembling miliary tuberculosis. The diagnosis of disseminated cryptococcosis was made based on transbronchial lung biopsy with subsequent detection of Cryptococcus neoformans in blood and cerebrospinal fluid. The patient was treated with liposomal amphotericin B as induction therapy, followed by fluconazole as consolidation and maintenance therapies thereafter. The infection was improved immediately, and he successfully underwent hematopoietic stem cell transplantation. The present case serves as a timely reminder that a radiological miliary pattern necessitates a thorough search for a definitive microbiological and histopathological diagnosis.